Examining Dutch disease across Australian regions. (19th September 2018) - Shafiullah, Muhammad; Selvanathan, Saroja; Naranpanawa, Athula; Chai, Andreas
Abstract: The recent mining boom represents one of the largest external shocks to the Australian economy in its post‐war history. Although most agree that it had a positive effect on the Australian economy as well as on people's living standards, there is disagreement over the extent to which this boom has caused deindustrialisation and the so‐called Dutch disease in Australia. Our empirical findings support the presence of Dutch disease nationally for Australia using data for the period 1984–2013. Regionally, the results show that Dutch disease was concentrated mainly in the eastern and southern states of Australia—Victoria, Queensland, South Australia and Tasmania.